Preparation method of high-rate lithium iron phosphate
By coating and doping the anhydrous iron phosphate in lithium iron phosphate material, and adding lithium source, carbon source and additives for carbon coating and sintering, the problem of improving the conductivity and rate performance of lithium iron phosphate materials is solved, and the preparation of high-rate lithium iron phosphate is achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411800991.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-08
AI Technical Summary
Due to the structure and properties of the material, lithium iron phosphate materials have low conductivity. Traditional improvement methods such as carbon coating and metal doping can only act on the surface, making it difficult to improve the conductive and rate performance of the material.
During the preparation of anhydrous iron phosphate, the intermediate product ferric phosphate is coated and doped and modified to form doped porous anhydrous iron phosphate, and on the basis of which the lithium source, carbon source and additives are added for secondary carbon coating and sintering, thereby preparing high-ratio lithium iron phosphate.
Through the modified anhydrous iron phosphate, the rate performance of lithium iron phosphate material is significantly improved and the energy density is maintained, which is suitable for a variety of application scenarios.
Smart Images

Figure CN119774573A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a method for preparing high-rate lithium iron phosphate. Background Art
[0002] Lithium iron phosphate batteries are gradually gaining favor in the market with their low price, high safety and long cycle performance. As the application scenarios become more and more diverse, people have higher and higher requirements for battery performance. In addition to maintaining a certain discharge capacity, batteries also need to have good rate performance to meet people's different needs for batteries, such as fast-charging cars, fast-charging tools, start-stop power supplies, etc.
[0003] However, due to the original structure and properties of lithium iron phosphate materials, their conductivity is not high. Traditional methods improve materials by carbon coating, metal doping and nano-improvement, but the raw material iron phosphate for preparing lithium iron phosphate generally has large and solid secondary particles. In the traditional preparation process, carbon coating and doping can only act on the surface of the material particles. It is still difficult for the material at the center of the particles to perform ion deintercalation and electron conduction during charging and discharging, resulting in limited improvement in the material's conductivity and rate performance. Summary of the invention
[0004] The present invention provides a method for preparing high-rate lithium iron phosphate. During the preparation of anhydrous iron phosphate, the intermediate product dihydrate iron phosphate is coated and doped to change the morphology and properties of the prepared anhydrous iron phosphate, thereby improving the rate performance of the material after the lithium iron phosphate is prepared.
[0005] The technical solution of the present invention is to provide a method for preparing high-rate lithium iron phosphate, comprising the following steps: S1, dispersing ferric phosphate dihydrate with water, then adding a carbon source and an additive, mixing the obtained slurry and drying it to obtain a powder; S2, the powder is sintered in an air furnace to obtain doped porous anhydrous iron phosphate; S3. Add lithium source, carbon source, additives and water to doped porous anhydrous iron phosphate and mix well to obtain slurry, grind and dry into powder, place in atmosphere furnace for sintering, and obtain high-rate lithium iron phosphate.
[0006] Optionally, the mass ratio of ferric phosphate dihydrate, carbon source and additive in S1 is 100:1~10:0~1.
[0007] Optionally, the carbon source is one or more of glucose, sucrose, starch, polyethylene glycol, citric acid or polyacrylonitrile.
[0008] Optionally, the additive is one or more of titanium dioxide, magnesium titanate, magnesium oxide, magnesium hydroxide, ammonium metavanadate, aluminum oxide or niobium oxide.
[0009] Optionally, the sintering temperature in S2 is 500-800° C., and the holding time is 3-8 hours.
[0010] Optionally, the amount of lithium source in S3 is determined according to the iron content in the doped porous anhydrous iron phosphate to ensure that the molar ratio of lithium element to iron element Li / Fe is 1.01-1.06.
[0011] Optionally, the mass ratio of the doped porous anhydrous ferric phosphate, the carbon source and the additive in S3 is 100:1~10:0.1~1. Optionally, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate, or lithium dihydrogen phosphate.
[0012] Optionally, S3 satisfies at least one of the following: The D50 of the ground material is controlled at 0.2~0.6μm; The sintering temperature is 700-800℃, the holding time is 6-14h; the sintering atmosphere is nitrogen; The sintered material is crushed to a finished particle size of D50: 1.5±1μm.
[0013] The present invention also relates to high-rate lithium iron phosphate obtained by the method.
[0014] The present invention has the following beneficial effects: The present invention uses dihydrated ferric phosphate as the starting point for modification. In the process of preparing anhydrous ferric phosphate from dihydrated ferric phosphate, a carbon source and an additive are added, wherein the carbon source can control the fusion and growth of ferric phosphate crystals, and the dopant can dope the inside of the ferric phosphate. The carbon source and the additive are used to pre-coat and pre-dope the ferric phosphate, and then the ferric phosphate is sintered in an air atmosphere. The carbon source volatilizes after high-temperature sintering to leave a large number of holes, thereby obtaining a doped porous anhydrous ferric phosphate. After secondary carbon coating and sintering in an oxygen-free atmosphere furnace, the material has better electronic conductivity and ionic conductivity, thereby preparing a high-rate lithium iron phosphate.
[0015] The anhydrous iron phosphate in the present invention has a porous structure with a higher porosity than conventional anhydrous iron phosphate raw materials, and the carbon coating effect is better when preparing lithium iron phosphate, so that the prepared lithium iron phosphate material has high-rate performance; in addition, the lithium iron phosphate of the present invention also has a lower carbon content and a higher compaction density, which can ensure that the battery cell has a high-rate performance while maintaining a higher energy density, meeting the application of various working conditions.
[0016] The method provided by the present invention is simple to operate, does not require equipment modification, and can be implemented using only existing conventional production equipment, thus being suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the rate-type lithium iron phosphate prepared in Example 1 of the present invention, magnified 10,000 times; Figure 2 This is a SEM image of the rate-type lithium iron phosphate prepared in Example 1 of the present invention, magnified 20,000 times; FIG. 3 is a charge and discharge curve diagram of the rate-type lithium iron phosphate prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.
[0019] A method for preparing high-rate lithium iron phosphate comprises the following steps: S1, dispersing ferric phosphate dihydrate with water, then adding a carbon source and an additive, mixing the obtained slurry and drying it to obtain a powder; S2, the powder is sintered in an air furnace to obtain doped porous anhydrous iron phosphate; S3. Add lithium source, carbon source, additives and water to doped porous anhydrous iron phosphate and mix well to obtain slurry, grind and dry into powder, place in atmosphere furnace for sintering, and obtain high-rate lithium iron phosphate.
[0020] In some embodiments, the mass ratio of ferric phosphate dihydrate, carbon source and additive in S1 is 100:1-10:0-1, preferably 100:1-5:0.1-0.5.
[0021] In some embodiments, the carbon source is one or more of glucose, sucrose, starch, polyethylene glycol, citric acid or polyacrylonitrile, preferably glucose and polyethylene glycol.
[0022] In some embodiments, the additive is one or more of titanium dioxide, magnesium titanate, magnesium oxide, magnesium hydroxide, ammonium metavanadate, aluminum oxide, or niobium oxide, preferably titanium dioxide.
[0023] In some embodiments, the sintering temperature in S2 is 500-800°C, preferably 550-700°C, and the holding time is 3-8h, preferably 3-6h.
[0024] In some embodiments, the amount of lithium source in S3 is determined according to the iron content in the doped porous anhydrous iron phosphate to ensure that the molar ratio of lithium to iron Li / Fe is 1.01-1.06, preferably 1.03.
[0025] In some embodiments, the mass ratio of the doped porous anhydrous ferric phosphate, the carbon source and the additive in S3 is 100:1-10:0.1-1. Preferably, it is 100:5-8:0.1-0.5. In some embodiments, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate, or lithium dihydrogen phosphate, preferably lithium carbonate.
[0026] In some embodiments, the D50 of the ground material is controlled at 0.2-0.6 μm, preferably 0.3-0.5.
[0027] The sintering temperature is 700-800°C, and the holding time is 6-14h; the sintering atmosphere is nitrogen; preferably 740-780°C, 8-12h.
[0028] The sintered material is crushed to a finished product particle size D50 of 1.5±1 μm, preferably 1.2±0.3.
[0029] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0030] Example 1 Ferric phosphate dihydrate is placed in deionized water, and the solid content is adjusted to 40%. Then, glucose and polyethylene glycol are added, with the mass being 3% and 2% of the ferric phosphate dihydrate respectively, and then titanium dioxide is added, with the mass being 0.2% of the ferric phosphate dihydrate; the above slurry is fully stirred and dispersed for 30 minutes, and then spray-dried to obtain a powder.
[0031] The above powder is placed in an air furnace for high-temperature sintering. The sintering temperature is set to 650°C and the insulation time is set to 4 hours. After natural cooling, anhydrous iron phosphate powder is obtained.
[0032] The anhydrous ferric phosphate powder and lithium carbonate, glucose, polyethylene glycol and titanium dioxide are mixed in deionized water, the amount of lithium carbonate added is calculated according to Li / Fe=1.03, the weight of glucose, polyethylene glycol and titanium dioxide account for 7%, 3% and 0.2% of the weight of anhydrous ferric phosphate respectively, the solid content of the slurry is controlled at 40%, and then the slurry is sand-milled, and the particle size at the end of sand-milling is D50: 0.4±0.5um; the above slurry is spray-dried to obtain a powder, and the powder is placed in a graphite sagger, and high-temperature sintering is carried out in a nitrogen-protected atmosphere furnace, the oxygen content of the kiln is <5ppm, the sintering temperature is 750℃, the insulation time is 9h, and the temperature is naturally reduced.
[0033] The sintered material is crushed to D50: 1.2±0.3um to obtain a high-rate lithium iron phosphate finished material.
[0034] The SEM images of the obtained materials are shown in Figures 1 and 2. Figure 1 and Figure 2It can be seen that the rate-type lithium iron phosphate particles in this embodiment are small and have a high specific surface area, which can shorten the lithium ion conduction distance inside the particles and increase the transmission interface with the electrolyte, thereby improving the material rate performance.
[0035] In addition, the high-rate lithium iron phosphate prepared in Example 1, SP (conductive agent carbon black) and PVDF (polyvinylidene fluoride) were mixed in NMP (N-methylpyrrolidone) at a mass ratio of 80:10:10 to prepare a slurry, and the slurry was coated on aluminum foil, dried, and sliced to prepare a working electrode. The surface density of the composite electrode material is 6.5 mg•cm -2 .
[0036] Test method: The lithium sheet in the lithium-ion half-cell is used as the reference electrode, and the electrolyte is a mixture of 1M lithium hexafluorophosphate ethylene carbonate / dimethyl carbonate (mass ratio 1:1); the battery charge and discharge test is carried out on the Xinwei battery test system, the voltage range is 2.0-4.2V (vs Li+ / Li), and the charge and discharge rate is calculated according to the mass of the lithium phosphate material. The specific test results are shown in Table 1. Figure 3 is a battery charge and discharge curve. It can be seen from the figure that the battery prepared by this material has a high rate discharge performance and a stable voltage platform.
[0037] Example 2 Ferrous phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added in an amount of 2% and 2% of the ferrous phosphate dihydrate, respectively. Then, titanium dioxide was added in an amount of 0.2% of the ferrous phosphate dihydrate. The rest was the same as in Example 1.
[0038] Example 3 Ferric phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added in an amount of 2% and 1% of the ferric phosphate dihydrate, respectively. Then, titanium dioxide was added in an amount of 0.2% of the ferric phosphate dihydrate. Other steps were the same as in Example 1.
[0039] Example 4 Ferrous phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added in an amount of 1% and 1% of the ferrous phosphate dihydrate, respectively. Then, titanium dioxide was added in an amount of 0.2% of the ferrous phosphate dihydrate. The rest was the same as in Example 1.
[0040] Example 5 Ferrous phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added in an amount of 4% and 2% of the ferrous phosphate dihydrate, respectively. Then, titanium dioxide was added in an amount of 0.2% of the ferrous phosphate dihydrate. The rest was the same as in Example 1.
[0041] Example 6 Ferric phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added in an amount of 3% and 2% of the ferric phosphate dihydrate, respectively. Then, titanium dioxide was added in an amount of 0.1% of the ferric phosphate dihydrate. Other steps were the same as in Example 1.
[0042] Example 7 Ferrous phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added in an amount of 3% and 2% of the ferrous phosphate dihydrate, respectively. Then, titanium dioxide was added in an amount of 0.3% of the ferrous phosphate dihydrate. Other steps were the same as in Example 1.
[0043] Comparative Example 1 Ferric phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. Then, glucose and polyethylene glycol were added, with the mass being 3% and 2% of the ferric phosphate dihydrate respectively. Titanium dioxide was not added. Other steps were the same as in Example 1.
[0044] Comparative Example 2 Ferric phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%. No carbon source was added, and only titanium dioxide was added, with a mass of 0.2% of the ferric phosphate dihydrate; the rest was the same as in Example 1.
[0045] Comparative Example 3 Ferric phosphate dihydrate was placed in deionized water, and the solid content was adjusted to 40%, without adding other substances; the rest was the same as in Example 1.
[0046] Table 1 (unit: mAh / g)
[0047] It can be seen from Table 1 above that the rate performance of the battery prepared by the materials in the examples is generally higher than that in the comparative examples, especially at high rates, the discharge performance of the examples is significantly better than that of the comparative examples. Secondly, in the examples, the discharge capacity of adding a carbon source or additive alone is poorer than that of adding in combination, and after increasing the amount of carbon source and doping in Examples 5 and 7, the improvement of high rate discharge capacity is limited, so the solution of Example 1 is relatively better.
[0048] In summary, the technical solution in the present invention has a significant effect on improving the rate performance of lithium iron phosphate materials, and the equipment and raw materials used in the solution are all used in existing conventional industrial processes, without the need to add other special equipment. It is relatively easy to scale up and put into production, and has great application prospects.
[0049] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing high-rate lithium iron phosphate, characterized in that: The following steps are involved: S1, dispersing ferric phosphate dihydrate with water, then adding a carbon source and an additive, mixing the obtained slurry and drying it to obtain a powder; S2, the powder is sintered in an air furnace to obtain doped porous anhydrous iron phosphate; S3. Add lithium source, carbon source, additives and water to doped porous anhydrous iron phosphate and mix well to obtain slurry, grind and dry into powder, place in atmosphere furnace for sintering, and obtain high-rate lithium iron phosphate.
2. The method according to claim 1, characterized in that: The mass ratio of ferric phosphate dihydrate, carbon source and additive in S1 is 100:1~10:0~1.
3. The method according to claim 1, characterized in that: The carbon source is one or more of glucose, sucrose, starch, polyethylene glycol, citric acid or polyacrylonitrile.
4. The method according to claim 1, characterized in that: The additive is one or more of titanium dioxide, magnesium titanate, magnesium oxide, magnesium hydroxide, ammonium metavanadate, aluminum oxide or niobium oxide.
5. The method according to claim 1, characterized in that: The sintering temperature in S2 is 500-800°C and the holding time is 3-8h.
6. The method according to claim 1, characterized in that: The amount of lithium source in S3 is determined according to the iron content in the doped porous anhydrous iron phosphate to ensure that the molar ratio of lithium to iron Li / Fe is 1.01-1.
06.
7. The method according to claim 1, characterized in that: The mass ratio of doped porous anhydrous ferric phosphate, carbon source and additive in S3 is 100:1~10:0.1~1.
8. The method according to claim 1, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate, or lithium dihydrogen phosphate.
9. The method according to any one of claims 1 to 7, characterized in that: S3 satisfies at least one of the following: The D50 of the ground material is controlled at 0.2~0.6μm; The sintering temperature is 700-800℃, the holding time is 6-14h; the sintering atmosphere is nitrogen; The sintered material is crushed to a finished particle size of D50: 1.5±1μm.
10. High-rate lithium iron phosphate obtained by the method according to any one of claims 1 to 9.